2005
DOI: 10.1016/j.jhep.2005.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Keeping cool in acute liver failure: Rationale for the use of mild hypothermia

Abstract: Encephalopathy, brain edema and intracranial hypertension are neurological complications responsible for substantial morbidity/mortality in patients with acute liver failure (ALF), where, aside from liver transplantation, there is currently a paucity of effective therapies. Mirroring its cerebro-protective effects in other clinical conditions, the induction of mild hypothermia may provide a potential therapeutic approach to the management of ALF. A solid mechanistic rationale for the use of mild hypothermia is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 168 publications
(181 reference statements)
0
25
0
3
Order By: Relevance
“…11,23,24 In ALF as in other critical illness, MOF is associated with high circulating levels of proinflammatory cytokines and other modulators of vascular function; [25][26][27] the effects of these agents on cerebral endothelial and vascular function could be important factors in the pathogenesis of ICH. 5,28,29 The observation of an increased incidence of ICH in the young was reported in the original description of this complication. 30 Although we confirmed this observation, we found no association between age and the development of HE.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…11,23,24 In ALF as in other critical illness, MOF is associated with high circulating levels of proinflammatory cytokines and other modulators of vascular function; [25][26][27] the effects of these agents on cerebral endothelial and vascular function could be important factors in the pathogenesis of ICH. 5,28,29 The observation of an increased incidence of ICH in the young was reported in the original description of this complication. 30 Although we confirmed this observation, we found no association between age and the development of HE.…”
Section: Discussionmentioning
confidence: 93%
“…[4][5][6] The net result of these changes is a marked alteration in cerebral function and astrocytic swelling. [5][6][7] Recent studies reporting circulating ammonia concentrations in patients with ALF have found levels higher than those seen in patients with HE accompanying chronic liver disease (CLD). 2,3,8,9 The magnitude of the elevation of ammonia, particularly if it is above 150 mol/L, has been reported to be related to an increased risk of major cerebral complications, including reduced consciousness level, seizures, cerebral herniation (CH), and death.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Motor and EEG changes were followed within 24 h after administration of the last dose of TAA. Because hypothermia may be a side effect of TAA treatment, that may protect the development of HE in acute liver failure (46,57); rectal temperature was monitored during the same period.…”
mentioning
confidence: 99%
“…Hepatic encephalopathy and brain edema leading to intracranial hypertension are 2 major complications in patients with acute liver failure [135]. It is estimated that 20% of patients with acute liver failure die from increased ICP while awaiting transplantation.…”
Section: Hepatic Encephalopathymentioning
confidence: 99%